LEGAL MEASURES TO OVERCOME THE CRIME OF MONEY LAUNDERING COMMITTED BY THE INDONESIAN NATIONAL ARMY (TNI) - Karolus Agung Dery Rianto; Rahmayanti; Muhammad Arif Sahlepi (Journal of International Islamic Law, Human Right and Public Policy, 2024)
The motive for committing the crime of money laundering is one form of modern crime whose existence is very detrimental to national interests, money laundering is a derivative crime from a predicate crime, the motive for committing money laundering is to disguise assets which are the proceeds of crimes so that they appear to originate from legitimate means, making it difficult for law enforcement authorities to make disclosures. As for the discussion that will be discussed in this research, Criminal Responsibility for Military Members Who Commit Money Laundering Crimes and the Efforts Made by the Indonesian National Army in Combating Money Laundering Crimes. The research method used is the Normative Juridical method with a descriptive analysis approach. The results of this research are that accountability for the TNI who commit criminal acts of money laundering must continue to be processed legally as it should be for non-civil society in accordance with the provisions of Law no. 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering (TPPU) and the efforts made by the TNI to tackle TPPU by improving the financial system within the scope and designing it systematically to avoid TPPU carried out by TNI members themselves.